Erythrocyte Amyloid Beta Peptide Isoform Distributions in Alzheimer and Mild Cognitive Impairment - Järemo, Petter; Jejcic, Alenka; Jelic, Vesna; Shahnaz, Tasmin; Oweling, Magnus; Winblad, Bengt; Behbahani, Homira (Current Alzheimer research, 2019)
We recently showed that Amyloid Beta (Aβ)40 accumulates in erythrocytes and possibly causes cell damage as evidenced by an increased number of assumed injured low-density (kg/L) erythrocytes. Furthermore, we have suggested a separation technique to isolate and concentrate such damaged red blood cells for subsequent analysis. We isolated high- and low-density erythrocytes and investigated the accumulation patterns of the Aβ peptides (Aβ40, Aβ42, and Aβ43) in Alzheimer (AD), mild cognitive impairment (MCI), and Subjective Cognitive Impairment (SCI). Whole blood was fractionated through a density gradient, resulting in two concentrated highand presumed injured low-density erythrocyte fractions. After cell lysis, intracellular Aβ40, Aβ42, and Aβ43 were quantified by ELISA. In both high- and low-density erythrocytes, Aβ40 displayed the lowest concentration in MCI, while it was equal and higher in AD and SCI. Aβ40 was detected at a 10-fold higher level than Aβ42, and in injured low-density erythrocytes, the lowest quantity of Aβ42 was found in AD and MCI. Aβ40 exhibited a 100-fold greater amount than Aβ43, and lighter erythrocytes of MCI subjects displayed less intracellular Aβ43 than SCI. Red blood cell accumulation patterns of Aβ40, Aβ42, and Aβ43 differ significantly between AD, MCI, and SCI. The data must be verified through larger clinical trials. It is, however, tenable that Aβ peptide distributions in erythrocyte subpopulations have the potential to be used for diagnostic purposes.